Librarian and Faculty Collaboration in Honors 301.88: An Interdisciplinary Computer Applications Course - Woodard, Patricia (Research strategies, 1996)
Hunter College librarians and faculty collaborated in an interdisciplinary honors survey designed to familiarize undergraduates with electronic research tools and with statistical, geographical, desktop publishing, and graphics software. Participating librarians cited consumption of staff time, lack of a chain of command, and communications problems as areas needing consideration in course planning and implementation. (PEN)